2015
DOI: 10.1097/npt.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contributions of Training Intensity on Locomotor Performance in Individuals With Chronic Stroke

Abstract: This study provides the first evidence that the intensity of locomotor practice may be an important independent determinant of walking outcomes poststroke. In the clinical setting, the intensity of locomotor training can be manipulated in many ways, although this represents only 1 parameter to consider.Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A90).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…For example, aerobic capacity effect sizes in previous studies (AEX group change minus control group change) have ranged from −1.5 13 to +6.3 14 mL/kg/min, walking speed effect sizes have ranged from −0.09 15 to +0.25 16 m/s and walking endurance (6-minute walk test) effect sizes have ranged from −25 17 to +89 16 m. An understanding of the factors affecting these between study differences could help inform AEX prescription and prioritize future studies.…”
Section: Main Manuscriptmentioning
confidence: 99%
“…For example, aerobic capacity effect sizes in previous studies (AEX group change minus control group change) have ranged from −1.5 13 to +6.3 14 mL/kg/min, walking speed effect sizes have ranged from −0.09 15 to +0.25 16 m/s and walking endurance (6-minute walk test) effect sizes have ranged from −25 17 to +89 16 m. An understanding of the factors affecting these between study differences could help inform AEX prescription and prioritize future studies.…”
Section: Main Manuscriptmentioning
confidence: 99%
“…In clinical practice, this represents a considerable resource saving compared with provision of MTD. Therefore, the design reported here may have advantages over that reported earlier [37].…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies have mainly used dose-ranging designs with pre-specified doses with parallel groups [35] or intervention crossover [36]. The authors are only aware of one previous dose-finding study of a rehabilitation intervention, but a different design was used to that reported here [37]. Unlike the present study, the starting dose was relatively high (only two cohorts before MTD was found: n=6), subsequent doses were not based on benefit as well as report of adverse consequences, each cohort received four different doses, de-escalation did not appear to have been considered and checking rules were not applied.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise, such as treadmill training, is continually used in rehabilitation due to its effectiveness in improving function, mobility and cardiovascular fitness in patients with chronic stroke (3739). Generally, this review shows that aerobic exercise is able to promote changes in central BDNF concentrations in animal models of stroke.…”
Section: Discussionmentioning
confidence: 99%